Caries prevalence and treatment needs of 7- to 10-year-old schoolchildren in southwestern Germany - Zerfowski, Martin; Koch, Martin Jean; Niekusch, Uwe; Staehle, Hans Jörg (Community dentistry and oral epidemiology, 1997)
The caries status of 1784 children aged 7 to 10 years was examined in a cross-sectional, epidemiological study in the Rhine-Neckar-District. Results showed that 30.5% of the children had caries-free primary and 65.2% had caries-free permanent teeth. The d(m)ft index was 2.68, and the D(M)FT averaged 0.76. As in previous studies, a high risk caries group was found, with 10% of all children showing more than 50% of all carious and filled teeth in the permanent dentition. Overall, 45.6% of the children's primary teeth and 16.3% of their permanent teeth needed treatment. As indicated by higher DT:F T (DT:FT) ratios in younger age groups, dentists preferred treating older children. Apart from a higher caries prevalence in primary teeth in males, no significant sex differences were found. Children of rural origin had a higher caries experience. The results confirm previous data showing considerable improvements with a declining caries experience in the young population. But the caries status of German pre-teenage children is still moderately high according to WHO criteria. For further improvements, considerable efforts have to be made with special emphasis on prevention in high risk caries groups.
Elektronische Reproduktion der Druck-Ausgabe
First published: 29 May 2006
Gesehen am 16.02.2021